UJI AKTIVITAS ANTIBAKTERI SEDIAAN GEL FACIAL WASH EKSTRAK DAUN SOKA (Ixora chinensis Lam.) TERHADAP BAKTERI Staphylococcus aerus ATCC 01055 - kartikawati, endah (Jurnal Sabdariffarma: Jurnal Ilmiah Farmasi, 2025)
Acne (acne) is a disease on the surface of the skin that is associated with excess production of oil glands (seeds). Acne can occur due to the obstruction of poly-base follicles caused by bacterial infections such as Staphylococcus aureus. Eighty percent of teenagers have experienced acne that's really disturbing their appearance and damaging everyone's self-confidence. Public awareness of the dangers posed by chemicals, in cosmetics, has shifted lifestyle changes along with the current Back to nature or lifestyle back to nature so many people believe in herbal cosmetic. Flavonoids are secondary metabolite compounds that have antibacterial activity against acne- causing Staphylococcus aureus. The initial step to prevent acne is to use facial wash that contains active compounds such as flavonoids. This study aims to find out that the facial wash gel preparation of soka leaf extract has antibacterial activity against Staphylococcus aureus bacteria. The preparation is made with extract concentrations of 5%, 10%, 15% preparation evaluation includes organoleptic tests, homogeneity tests, pH tests, foam stability testing, viscosity test, stability trials, gel preparation irritation tests, and antibacterial activity against Staphylococcus aureus. The results of the study show that the concentrations are 5%, 10% and 15% respectively of 11.03 mm, 13.60 mm, and 14.22 mm. Formula 3 has a high barrier zone with a concentration of 15% extract with an average barrier area of 14.22mm.Keywords: Leaves of soka, Gel facial wash, Staphylococcus aureus